A Review on the Morphologically Controlled Synthesis of Polyphosphazenes for Electrochemical Applications. Issue 5 (20th January 2021) - Ali, Zahid; Basharat, Majid; Wu, Zhanpeng
Abstract: Polyphosphazenes (PPNs) belong to organic‐inorganic hybrid polymeric skeletal materials suitably fabricated via precipitation or condensation polymerization and self‐assembly approaches. Organic moieties with two and three −NH2 or −OH functionalities inherit subsequent ordered 2D and 3D arrangements of the atoms and molecules to attain the morphologies such as nanotubes, nano/micro‐spheres, fibers, nanosheets, and covalent organic frameworks (COFs). Auto‐doping is a strategic feature of PPN materials to originate binary‐, ternary‐, and quaternary‐doped carbon frameworks and graphitic carbon nitride ( g ‐C3 N4 ) upon direct pyrolysis in an inert environment. Hollow carbon spheres provides a good range of surface areas (ca. 755–3673 m 2 /g) with enormous active sites and hierarchical channels for the effective flow of electrolyte ions, which make them a good choice for solid‐state batteries and supercapacitors; structural irregularities and imperfections offer surface‐adsorbed breakdown of water and open new horizons for water splitting through hydrogen evolution, oxygen evolution and oxygen reduction with the lowest half‐wave ( E 1/2 ) potential when compared to Pt/C‐ and Pt/C+RuO2 ‐based electrocatalysts. Abstract : Polyphosphazenes in practice : This Review presents an overview of the latest advancements in the fabrication, assembly, and pyrolytic behaviors of cyclo‐polyphosphazenes‐based micro‐ and nano‐architectures, including self‐assembly synthetic routes and surface morphological control from 0D‐3D, the phenomena of auto‐dopant character and co‐doped carbon attaining strategies, application‐based observations, as well as challenges and future perspectives.